Employing the Precautionary Principle to Evaluate the Use of E-Cigarettes - Bush, Ashley M.; Holsinger, James W.; Prybil, Lawrence D. (Frontiers in Public Health, 2016)
Electronic cigarettes have emerged onto the public market as an alternative to tobacco cigarettes; however, science is inconclusive as electronic cigarettes have not been thoroughly investigated, including their short- and long-term risks and benefits.1,2 The question arises of whether electronic cigarettes will become the future tobacco crisis. This paper connects the Precautionary Principle to the use of electronic cigarettes in an effort to guide decision-makers in the prevention of adverse health outcomes and societal costs.